Extending the Spectral Responsivity of MoS2 Phototransistors by Incorporating Up‐Conversion Microcrystals. Issue 21 (26th August 2018) - Zhang, Youwei; Wang, Jiao; Wang, Bing; Shao, Jinhai; Deng, Jianan; Cong, Chunxiao; Hu, Laigui; Tian, Pengfei; Liu, Ran; Zhang, Shi‐Li; Qiu, Zhi‐Jun
Abstract: Layered 2D semiconductors are characterized by unique photoelectric properties and, therefore, constitute a new class of basic building block for next‐generation optoelectronics. However, their wide bandgaps limit the spectral responsivity to a narrow range. Here, a facile approach is demonstrated by integrating β‐NaYF4 :Yb 3+, Er 3+ up‐conversion microcrystals (UCMCs) with monolayer‐MoS2 phototransistors to break this bandgap‐imposed barrier and to drastically extend the responsivity range. In essence, the UCMCs up‐convert a near‐infrared excitation at 980 nm to visible light of photons with energy matching the large bandgap (i.e., 1.8 eV) of monolayer‐MoS2, thereby activating the phototransistor with remarkable photocurrent and minimum interference. This approach leads to preservation of the excellent electrical merits of monolayer‐MoS2 and simultaneous retention of its low dark current and high photoresponsivity to the above‐bandgap lights. Significantly, an enhancement by over 1000 times is achieved for both responsivity and specific detectivity at 980 nm excitation. Moreover, the rate of response is kept identical to that when the MoS2 phototransistor is excited by a visible light. Therefore, integrating with UCMCs can enable the emerging 2D semiconductors of wide bandgap to respond to infrared excitations with high efficacy and without sacrificing their performance in the visible region. Abstract : A facile approach to breaking bandgap‐imposed barrier and to drastically extend the responsivity range to the near‐infrared region with a high enhancement is demonstrated. Key to this approach is to integrate β‐NaYF4 :Yb 3+, Er 3+ up‐conversion microcrystals with MoS2 phototransistors, leading to the desired extension with high photoresponsivity as well as the anticipated exploitation of the excellent electrical merits of MoS2 .